Genetically targeted fluorescent probes reveal dynamic calcium responses to adrenergic signaling in multiple cardiomyocyte compartments. (September 2019) - Luptak, Ivan; Morgan, Robert; Baka, Tomas; Croteau, Dominique; Moverman, Daniel; Sarnak, Hannah; Kirber, Michael; Bachschmid, Markus M.; Colucci, Wilson S.; Pimentel, David R.
Graphical abstract: Highlights: Updated toolkit to track Ca 2+ movements between cardiomyocyte sub-compartments. Norepinephrine (NE) increases Ca 2+ in sarcoplasmic reticulum and mitochondria. NE decreases Ca 2+ in mitochondria associated membrane space via MCU and SERCA. Ca 2+ uptake appears faster in mitochondria than in sarcoplasmic reticulum. Abstract: Calcium (Ca 2+ ), an important second messenger, regulates many cellular activities and varies spatiotemporally within the cell. Conventional methods to monitor Ca 2+ changes, such as synthetic Ca 2+ indicators, are not targetable, while genetically encoded Ca 2+ indicators (GECI) can be precisely directed to cellular compartments. GECIs are chimeric proteins composed of calmodulin (or other proteins that change conformation on Ca 2+ binding) coupled with two fluorescent proteins that come closer together after an increase in [Ca 2+ ], and enhance Förster resonance energy transfer (FRET) that allows for ratiometric [Ca 2+ ] assessment. Here, adult rat ventricular myocytes were transfected with specifically targeted calmodulin-based GECIs and Ca 2+ responses to a physiological stimulus, norepinephrine (NE, 10 μM), were observed in a) sarcoplasmic reticulum (SR), b) mitochondria, c) the space between the mitochondria and SR, termed the Mitochondria Associated Membrane space (MAM) and d) cytosol for 10 min after stimulation. In SR and mitochondria, NE increased the [Ca 2+ ] ratio by 17% and by 8%, respectively. In the MAM the [Ca 2+ ] ratio decreased by 16%, while in cytosol [Ca 2+ ] remained unchanged. In conclusion, adrenergic stimulation causes distinct responses in the cardiomyocyte SR, mitochondria and MAM. Additionally, our work provides a toolkit-update for targeted [Ca 2+ ] measurements in multiple cellular compartments.